2020
DOI: 10.36740/wlek202006119
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Postpartum Endometritis and Antimicrobial Resistance of Responsible Pathogens in Ukraine: Results a Multicenter Study (2015-2017)

Abstract: The aim: To obtain the prevalence of postpartum endometritis women and antimicrobial resistance of responsible pathogens in Ukraine. Materials and methods: We performed a retrospective multicenter cohort study. The study population consisted of all women who had a vaginal delivery or cesarean section in 14 Regional Women’s Hospitals of Ukraine. Results: Total 2460 of 25,344 patients were found to have postpartum endometritis, for an overall infection rate of 9.7%. The postpartum endometritis rates were 7.6% af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 12 publications
(23 reference statements)
0
23
0
1
Order By: Relevance
“…A ten-year surveillance study of pathogens implicated in urinary tract infections revealed a significant increase in the proportions of multidrug-resistant bacteria and fluoroquinolone-resistant E. coli [ 166 ]. The recent studies examined the prevalence of MRSA and Methicillin-resistant Staphylococcus epidermidis (MRSE) and ESBL production among Enterobacteriaceae in postpartum mastitis [ 167 ] and postpartum endometritis [ 168 ]. To date, molecular epidemiological studies are limited in Ukraine [ 169 , 170 ].…”
Section: A Snapshot Of Amr Surveillance Programs and The Epidemiologymentioning
confidence: 99%
“…A ten-year surveillance study of pathogens implicated in urinary tract infections revealed a significant increase in the proportions of multidrug-resistant bacteria and fluoroquinolone-resistant E. coli [ 166 ]. The recent studies examined the prevalence of MRSA and Methicillin-resistant Staphylococcus epidermidis (MRSE) and ESBL production among Enterobacteriaceae in postpartum mastitis [ 167 ] and postpartum endometritis [ 168 ]. To date, molecular epidemiological studies are limited in Ukraine [ 169 , 170 ].…”
Section: A Snapshot Of Amr Surveillance Programs and The Epidemiologymentioning
confidence: 99%
“…Infections at postpartum presents a significant burden to the hospital system and remains a significant cause of maternal mortality and morbidity worldwide ( 39 , 40 ), yet the epidemiology of several post-delivery pathologies including postpartum endometritis, postpartum sepsis and chorioamnionitis remains elusive and has not been well characterized. Postpartum endometritis (PPE) describes an inflammation or infection of the upper genital tract comprising the endometrium, myometrium, and the surrounding tissue.…”
Section: Methodsmentioning
confidence: 99%
“…One of the reasons for healthcare-associated infections is the wide spread of conditionally pathogenic microorganisms in Ukraine that are resistant to antibiotics [10,11]. The emergence and spread of antimicrobial resistance has become a major public health threat in Ukraine, and the number of infections caused by resistant pathogens causing of HARTIs continues to increase [12,13].…”
Section: Introductionmentioning
confidence: 99%